Hubungan Komitmen Organisasi dengan Kinerja Karyawan pada Yayasan Pendidikan Islam Terpadu Al-Muawanah - Faisal Sailistia; Raka Pria Anugrah; Farah Chalida Hanoum (Reslaj : Religion Education Social Laa Roiba Journal, 2020)
ABSTRACT Employee performance is an organizational key to achieving company goals. This study aims to determine the relationship between organizational commitment and employee performance of the Al-Muawanah Integrated Islamic Foundation. The research method used is a mixed method descriptive qualitative and quantitative approach with multiple regression. The results showed that organizational commitment, employee performance generally went well. There is a strong correlation between organizational commitment and employee performance with the Pearson correlation coefficient of 0.869. There is a positive and significant relationship between organizational commitment and the performance of Foundation employees. This means that the more positive the organizational commitment, the higher the employee performance of the Al-Muawanah Integrated Islamic Foundation Keywords: Organizational Commitment, Employee Performance, Islamic Foundation